User-Centered Virtual Reality for Promoting Relaxation: An Innovative Approach - Pizzoli, Silvia Francesca Maria; Mazzocco, Ketti; Triberti, Stefano; Monzani, Dario; Alcañiz Raya, Mariano Luis; Pravettoni, Gabriella (Frontiers in Psychology, 2019)
Virtual reality has been used effectively to promote relaxation and reduce stress. It is possible to find two main approaches to achieve such aims across the literature. The first one is focused on generic environments filled with relaxing “narratives” to induce control over one’s own body and physiological response, while the second one engages the user in virtual reality-mediated activities to empower his/her own abilities to regulate emotion. The scope of the present contribution is to extend the discourse on VR use to promote relaxation, by proposing a third approach. This would be based on VR with personalized content, based on user research to identify important life events. As a second step, distinctive features of such events may be rendered with symbols, activities or other virtual environments contents. According to literature, it is possible that such an approach would obtain more sophisticated and long-lasting relaxation in users. The present contribution explores this innovative theoretical proposal and its potential applications within future research and interventions.